2013
DOI: 10.1037/a0033453
|View full text |Cite
|
Sign up to set email alerts
|

Youth Offender Care Needs Assessment Tool (YO-CNAT): An actuarial risk assessment tool for predicting problematic child-rearing situations in juvenile offenders on the basis of police records.

Abstract: In the juvenile justice system, much attention is paid to estimating the risk for recidivism among juvenile offenders. However, it is also important to estimate the risk for problematic child-rearing situations (care needs) in juvenile offenders, because these problems are not always related to recidivism. In the present study, an actuarial care needs assessment tool for juvenile offenders, the Youth Offender Care Needs Assessment Tool (YO-CNAT), was developed to predict the probability of (a) a future supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Recently, an actuarial risk screening instrument (Youth Offender Care Needs Assessment Tool; YO-CNAT) was developed to provide Dutch police officers an indication of the risk for future care needs of juvenile offenders, which is needed for the decision to refer these juveniles for further assessment [ 4 ]. This instrument was specifically developed for young offenders and solely based on information available in the Dutch police system, so that it can be used by Dutch police officers who, in general, do not have a clinical background.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, an actuarial risk screening instrument (Youth Offender Care Needs Assessment Tool; YO-CNAT) was developed to provide Dutch police officers an indication of the risk for future care needs of juvenile offenders, which is needed for the decision to refer these juveniles for further assessment [ 4 ]. This instrument was specifically developed for young offenders and solely based on information available in the Dutch police system, so that it can be used by Dutch police officers who, in general, do not have a clinical background.…”
Section: Introductionmentioning
confidence: 99%
“…The items comprising the YO-CNAT are presented in Table 1 . Van der Put and Stams [ 4 ] showed that the discriminatory accuracy of this instrument ranged between acceptable (with an AUC value of .701) and good (with an AUC value of .745) for predicting different types of future care needs. The YO-CNAT was specifically developed for screening juvenile offenders, but police officers also come into contact with large numbers of juvenile non -offenders, who were involved in a criminal incident but not in the role of a suspect.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations